A ornamentação contemporânea em arte e design: função estética, anagógica, terapêutica - Pantaleão, Lucas Farinelli; Pinheiro, Olimpio José [UNESP] (My University, 2011)
Taking as a starting point the reflection on the ornament, is delineated an interpretative analysis of delimitation between art and design in the extent of the aesthetics. Presupposing the ornament as an elementary and universal form of the all aesthetics’ manifestations, trying to work, through recent contributions and in an unified way, concepts regarding the aesthetics in parallel with the phenomenon of the perception. The ornament as element previously “ordered” front to the organization need that the interpretation demands, it constitutes fertile philosophical instrument, for all the art forms and of design, which seeks to provide an aesthetic sensation. Returned to the thoughtful function, the ornament has as essential purpose to stimulate the aesthetic experimentation, capable to induce the perception to subtler states of conscience similar of to the ecstasy, where the spirit from whom contemplates, can live experiences of extreme freedom and intense pleasure. . Establishing semiotics foundations capable of evidencing a function anagogic-therapeutics in the action of conceiving and to meditating, alternately, an object with function strictly ornamental (aesthetics), also intending the reflection of moral stamp on the ornamental concept of the decency as conciliatory solution in the intersection between art and design, concerning the creativity of the formative process.

Delineia-se uma delimitação entre arte e design no âmbito da estética, tomando como ponto de partida a análise interpretativa e a reflexão sobre o ornamento. Pressupondo o ornamento como uma forma elementar e universal a todas as manifestações estéticas, procura-se trabalhar, através de contribuições recentes e de maneira unificada, conceitos referentes à estética em paralelo com o fenômeno da percepção. O ornamento como elemento previamente “ordenado” frente à necessidade de organização que a interpretação exige, constitui instrumento filosófico fecundo, para todas as formas de arte e de design, nas quais se visa proporcionar uma percepção estética. Voltado à função contemplativa, o ornamento tem como propósito essencial estimular a experienciação estética, capaz de induzir a percepção a estados de consciência mais sutis semelhantes ao do êxtase, onde o espírito daquele que contempla pode vivenciar experiências de extrema liberdade e intenso prazer. Estabelecendo fundamentos de semiótica capazes de evidenciar uma função anagógico-terapêutica no ato de conceber e contemplar, alternadamente, um objeto com função estritamente decorativa (estética), propõe-se uma reflexão de cunho moral sobre o conceito ornamental do decoro como solução mediadora na intersecção entre arte e design, no tocante à criatividade do processo formativo.
Keywords: Design of product; Art and design; Aesthetics; Ornamentation; Aesthetic effect; Anagogic; Therapeutic; Design de produto; Arte e design; Estética; Ornamentação; Efeito estético; Anagógico; Terapêutico